Antecedents of Knowledge Management Practices: Case of Malaysian Practitioners - Mohamed Jalaldeen Mohamed Razi; Mohd Izzuddin Mohd Tamrin; Abdul Rahman Ahmad Dahlan; Noor Azian Mohamad Ali (Bulletin of Electrical Engineering and Informatics, 2018)
In this paper, we investigated the knowledge management (KM) behavior of executives in Malaysia who work in different sectors and involved in Information Technology (IT) related fields. We proposed a conceptual framework based on the Theory of Reasoned Action (TRA), the Theory of Planned Behavior (TPB) and Unified Theory of Acceptance and Use of Technology (UTAUT) to study their intention and involvement in KM initiatives. The knowledge creation theory (SECI process) was employed to operationalize KM intention and KM behavior. We proposed six independent variables that represent the social-cultural nature of KM as the antecedence of KM intention. These variables are trust, management support, decentralization, IT support, performance expectancy (PE), and effort expectancy (EE). Seventy-four executives from both private and government-linked organizations responded to our online questionnaire. SmartPLS3 was used to run the analysis. The reliability was ensured with the factor loadings, Cronbach’s alpha, Composite Reliability (CR) that met the fit requirement of above 0.6, 0.7 and 0.7 respectively. The convergent validity was confirmed through average variance extracted (AVE) that met the fit requirement of above 0.5. The discriminant validity was assessed by using Fornell and Larcker’s criterion. Finally, the structural model confirmed that only PE of KM, and EE of KM are the significant predictors of KM intention and the KM intention significantly predicts KM behavior. The implications of the findings are discussed in detail at the end of the paper.